Cost-Effectiveness of Extracorporeal Photopheresis in Patients With Chronic Graft-vs-Host Disease - Adrian Peacock; Frances C. Dehle; Oscar A. Mesa Zapata; Francesca Gennari; Maro R.I. Williams; Nada Hamad; Stephen Larsen; Simon J. Harrison; Colman Taylor (Journal of Health Economics and Outcomes Research)
**Background:** The mainstay first-line therapy for chronic graft-vs-host disease (cGVHD) is corticosteroids; however, for steroid-refractory patients, there is a distinct lack of cost-effective or efficacious treatment. The aim of this study was to assess the cost-effectiveness of extracorporeal photopheresis (ECP) compared with standard-of-care therapies for the treatment of cGVHD in Australia. The study formed part of an application to the Australian Government to reimburse ECP for these patients.